PENGARUH KADAR EKSTENDER TEPUNG BIJI ALPUKAT TERHADAP MUTU KAYU LAPIS DAMAR (Agathis alba Foxw) - M. I. Iskandar; Achmad Supriadi (BRIN Publishing, 2016)
The addition of extender in the adhesive mixture may reduce the cost of gluing in the plywood manufacture. The extender addition should not reduce the plywood quality in term of internal bonding. This paper examines the use of avocado seeds flour as an extender in the manufacture of damar plywood (Agathis alba Foxw.). Based on the total mixture weight, the seeds flour was grouped into three concentrations of 10%, 20% and 30%. The main adhesive used was Urea Formaldehyde (UF) and parameters tested includes moisture content, density and internal bonding strength. Results show that the average of plywood moisture content, density and internal bonding strength were 7.46%, 0.48 g/cm , 11.77 kg/cm , respectively. The moisture content and bonding strength of damar plywood meets the Indonesian National Standard (SNI). The maximum bonding strength was achieved by plywood with an extender of 10% avocadoseed's flour. The variation of extender contents shows the pattern of the greater the extender content the the lower the internal bonding strength.